Screening of differentially expressed proteins from syncytiotrophoblast for severe early-onset preeclampsia in women with gestational diabetes mellitus using tandem mass tag quantitative proteomics - Xiaotong Sun; Tao Qu; Xiyan He; Xueping Yang; Nan Guo; Yan Mao; Xianghong Xu; Xiaodong Sun; Xuehong Zhang; Weihua Wang (BMC, 2018)
Abstract Background Previous studies have revealed that women with gestational diabetes mellitus (GDM) have an increased risk of developing preeclampsia (PE). The possible reason is the abnormal lipid metabolism caused by GDM that leads to dysfunction of vascular endothelial cells and atherosclerosis, resulting in the onset of PE. However, studies focusing on the pathogenesis of PE in syncytiotrophoblast of GDM patients are lacking. This study aimed to compare differentially expressed proteins from syncytiotrophoblast between women with GDM and women with GDM with subsequently developed PE. Methods Syncytiotrophoblast samples were obtained from pregnant women immediately after delivery. To explore the protein expression changes of syncytiotrophoblast that might explain the pathogenesis of PE in women with GDM, quantitative proteomics was performed using tandem mass tag (TMT) isobaric tags and liquid chromatography-tandem mass spectrometry. Bioinformatics analysis was performed to enrich the biological processes that these differentially expressed proteins were involved in. Results A total of 28,234 unique peptides and 4140 proteins were identified in all samples. Among them, 23 differentially expressed proteins were identified between patients with GDM and patients with GDM with subsequently developed PE. Therein, 11 proteins were upregulated and 12 proteins were downregulated. Two relative proteins (FLT1 and PABPC4) were independently verified using immunoblotting analysis. Bioinformatic results indicated that the onset of PE in patients with GDM is a multifactorial disorder, involving factors such as apoptosis, transcriptional misregulation, oxidative stress, lipid metabolism, cell infiltration and migration, and angiogenesis. Conclusion These results indicated that the inadequacy of endometrium infiltration, angiogenic disorder, and oxidative stress in syncytiotrophoblast are more likely to occur in patients with GDM and may be the potential mechanisms leading to such patients secondarily developing severe early-onset PE.